Material Composition And Reservoir Properties Of Terrigenous Deposits (Eurasian Research Bulletin, 2024)
The article discusses the research work of a comprehensive analysis of the geological structure and oil and gas content of the southeastern part of the Chorzhui-Terrigen formation deposits and their prospects for the future. Based on the data obtained, recommendations are given for complex geological, geophysical and deep drilling operations.